Pengaruh Peran Ayah Terhadap Adaptasi Sosial Pada Anak Usia Dini Di Yayasan Nurmala Hati Jakarta Timur - Rabiah Al Adawiyah; Nita Priyanti (UIN Sultan Maulana Hasanuddin Banten, 2021)
People's perceptions of parenting that prioritize mothers over fathers are starting to shift. Along with the development of parenting science makes father involvement began to be applied in family education. The role of the father is needed in the process of child development. Based on previous research, the involvement of fathers in parenting in early childhood is still limited to responsibilities and decision holders that result in the presence of fathers who are limited to physical but not emotional. This research uses a quantitative approach. This study aims to find out the influence of the role of fathers on social adaptation in early childhood at The Nurmala Hati Foundation in East Jakarta. Based on the results of the study, the significance value of p = 0.000 and the correlation value (r) of 0.498 which means that there is a significant moderate influence between the role of fathers on social adaptation in early childhood, while the value of R square (r²) was obtained by 0.248 which shows that the percentage of the influence of father's role on social adaptation in early childhood is 24.8% at nurmala hati Foundation in East Jakarta. Keywords: father's role; social adaptation; Early childhood References Christine McWayne , Jason T. Downer , Rodrigo Campos & Robby D. Harris (2013) Keterlibatan Ayah Selama Anak Usia Dini dan Kaitannya dengan Pembelajaran Dini Anak: Analisis Meta, Pendidikan Dini dan Perkembangan, 24:6, 898-922. Emzir (2015). Metodologi Penelitian Pendidikan: Kuantitatif dan Kualitatif. (Edisi I Revisi). Jakarta: Rajawali Pers Febri Giantara, Kusdani, Santi Afrida. (2019). Peran Ayah Dalam Pendidikan Keluarga di Kota . Volume 2 Nomor 2, Desember 2019, 235-245. Hurlock, Elizabeth B. (2016). Perkembangan Anak. Jilid dua edisi enam. Jakarta: Erlangga. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Lamb, Michael E. (2011). The role of Father in Child Development, edisi enam, New Jersey: john Wiley a Sons, Inc. Nila A. Ulfa.2017. Hubungan peran ayah dengan penyesuaian diri anak usia 4-6 tahun di desa Gelang kecamatan Rakit Banjarnegara. Skripsi. Universitas Negeri Semarang. Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918 Nurjiddin. (2016). Penafsiran Sosiologis Terhadap Kepemimpinan Lelaki Dalam Al-Quran. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 6(1), 42–48. Nursyamsi N. Lalla, Trimaya C. Mulat, Nur Srianingsih. (2020). Perkembangan Adaptasi Sosial Anak Usia DIni dan Pola Asuh Orang Tua. Vol 11, No,1, Juni 2020, 468-471. Oberg, K. (1960). Culture Shock:Adjustment to New Cultural Enviroment. In Practical Anthropology, 7, (pp. 177-182). Palkovitz, R. (2002). Involved fathering and child development: Advancing our understanding of good fathering. In C. S. Tamis-Le Monda & N. Cabrera (Eds.), Handbook of father involvement: Multi-disicplinary perspectives (pp.119 – 140). Mahwah, New Jersey: Lawrence Erlbaum Associates Putri, A. S. (2019) Survei: Tak hanya ibu, kini ayah milenial lebih terlibat dalam pengasuhan anak. http //www.fimelia.com/parenting/read/4022850/survei-tak-hanya-ibu-kini-ayah-milenial-lebih-terlibat-dalam-pengasuhan-anak. Diakses pada: 19 Agustus 2021. Rob Palkovitz and James Hull (2018). Toward a Resource Theory of Fathering. Journal of Family Theory & Review Salvin E. Robert. Psikologi Pendidikan: Teori dan Praktik (Educational Psycology: Theory and Prcatice). Penerjemah: Samosir Marianto. 2008. PT. Macanan Jaya Cemerlang Santoso, F. S. (2020). Lingkungan Keluarga Sebagai Awal Pengembangan Kewirausahaan Islam. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 13–22. https://doi.org/10.47200/jnajpm.v5i1.418 Santrock, J. W. (2007). Perkembangan anak, edisi ke sebelas. Jakarta: Erlangga. Sulistyawati, L. (2019). KPAI: Peran Ayah Jadi Kunci Tumbuh Kembang Anak. Jakarta: Republika.co.id. Diakses pada: 28 Agustus 2021. The fathers.com. “The Extent of Fatherlessness”. The extent of fatherlessnes- National Center for Fathering (fathers.com). Diakses pada : 22 Agustus 2021. Thérèse Besnard & Marie-Josée Letarte (2017) Pengaruh Praktik Pendidikan Guru PAUD Pria dan Wanita Terhadap Adaptasi Sosial Anak, Journal of Research in Childhood Education, 31:3, 453-464.